Internalisasi Nilai-Nilai Religius untuk Membentuk Akhlak Siswa di MTS Islahiyah Kalitidu Bojonegoro - Ahmad Muthi’ Uddin; Mahmud Samsuri; Emma Rahmawati; Putri Nihayatun Nikmah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Globalization is indicated by the development of science and technology (IPTEK) which is increasingly advanced and rapid. It presents the era of digitalization which has a negative influence on one's attitudes and behavior if not used properly it will fade spiritual values ​​in individuals such as brawls, bullying and so on. So that education is believed to be able to build the spirituality of students for the better. In eradicating this, MTs Islahiyah Kalitidu carries out a process of internalizing the spiritual values ​​of students to form the morals of madrasas through various programs that have been prepared to have faith and hold fast to Islamic spiritual values.This study uses a qualitative approach with a descriptive approach. Data was collected by means of interview, observation and documentation techniques. Techniques in data analysis include data, data presentation to see the overall picture or certain parts of the research and drawing conclusions to obtain evidence that supports the data collection stage.Based on the research conducted, the following results were obtained: First, the strategy in the formation of akhlaq karimah by doing daily habituation through religious activities and adding hours of learning PAI material through the habituation method, the exemplary method, the lecture method, the punishment method and the reward. Second, Supporting Factors in the formation of morals, namely the process of daily habituation, good interaction between teachers and students, supporting facilities and infrastructure. Third, inhibiting factors, family environment, school environment and information media.